2021
DOI: 10.1038/s41598-021-97024-w
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism and topology in Tb-based icosahedral quasicrystal

Abstract: Quasicrystal (QC) possesses a unique lattice structure with rotational symmetry forbidden in conventional crystals. The electric property is far from complete understanding and it has been a long-standing issue whether the magnetic long-range order is realized in the QC. The main difficulty was lack of microscopic theory to analyze the effect of the crystalline electric field (CEF) at the rare-earth atom in QCs. Here we show the full microscopic analysis of the CEF in Tb-based QCs. We find that magnetic anisot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…We have shown that various magnetic states appear in the ground state of the IC [37,38]. Among them, we have found topological magnetic textures which are characterized by the non-trivial topological invariant, i.e., the topological charge.…”
Section: Topological Magnetic Texture On Icmentioning
confidence: 91%
See 3 more Smart Citations
“…We have shown that various magnetic states appear in the ground state of the IC [37,38]. Among them, we have found topological magnetic textures which are characterized by the non-trivial topological invariant, i.e., the topological charge.…”
Section: Topological Magnetic Texture On Icmentioning
confidence: 91%
“…Next, to get insight into the CEF in the QC Au-Ga-Tb, we have analyzed the CEF at the Tb site in the Tsai-type cluster [37,38]. The Tb 3+ ion with 4f 8 configuration is regarded to have the charge q = 6|e| in the hole picture since 4f 14 configuration is the closed shell of the 4f electrons.…”
Section: Crystalline Electric Field In Rare-earth Based Qc and Acmentioning
confidence: 99%
See 2 more Smart Citations
“…This has succeeded in formulating the full CEF Hamiltonian of any rare-earth ion in terms of the total angular momentum, which enables us to analyze the CEF accurately. By applying this formulation to the QC Au–SM–Tb and the AC, the CEF has been analyzed theoretically 31 , 32 . Then, it has been revealed that the magnetic anisotropy arising from the CEF plays a key role in realizing unique magnetic states on the icosahedron (IC) at whose vertices the Tb atoms are located.…”
mentioning
confidence: 99%